Confucian sociology of managerial knowledge - M. Yu. Zakharov; A. A. Komarova; O. V. Kryshtanovskaya (Вестник университета)
The article attempts to conceptualize the nature of managerial knowledge in traditional Chinese culture and the possibility of using methodological potential of current sociology of knowledge for this task. The role and significance of cognitive problematics in the history of old China have been formulated, Confucian type of knowledge has been analyzed; the placein this ancient management knowledge has been considered a statement on formation of predetermination of social consciousness of the Chinese has been substantiated. A conclusion on historical significance, productiveness and potential of Confucian sociology for formation of sociocultural mechanism of management of China has been made.